Pengaruh Citra Merk Dan Harga Jual Terhadap Ketertarikan Dan Keputusan Siswa Untuk Kuliah Di Kampus XYZ Sumatera Utara - Asmaul Husna; Sri Eka Wulandari; Metya Lutviani (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
With the increasing number of campuses in North Sumatra, XYZ Campus must maintain its quality so that it continues to be the trust of its prospective students. Many prospective students in making their decisions usually consider the brand image, they will choose a well-known and reliable place of study from lesser-known campuses. The problem to be studied is the decreasing number of students who make XYZ Campus a place for lectures. The type of research used is a type of quantitative research. The research sample used in this study was a census or saturated sampling. The population is all new students of XYZ Campus. From the results of data processing, obtained a significance value of 0.0 which is smaller than 0.05 and based on the calculated F value of 15.270 which is greater than the F table of 3.18. From the two analyzes, Ho is rejected, meaning that there are simultaneously independent variables affecting the dependent variable. To increase the number of students, XYZ Campus must improve its Brand Image and estimate an Affordable Selling Price. Adjusted R Square value is 0.346 or 34.6%. This condition explains that 34.6% of the brand image and selling price variables affect the campus selection decision.